The articulation of the Community of Inquiry Framework in the Online Discussion - Hatmanto, Endro Dwi; Widi Pratolo, Bambang (International Journal of Psychosocial Rehabilitation, 2020)
With the emergence of blended learning environment, lecturers have to be capable of teaching successfully. One of the strategies is by cultivating the learning community which requires lecturers to be the facilitators of learning and students to be active participants in the learning process. The learning community finds its ideal format in the community of inquiry (CoI) framework consisting of teaching, social and cognitive presence. The manifestation of the CoI is the implementation online discussion. This research aims to reveal the advantages of using online discussion and the extent to which the CoI principles had been present in the online discussion. Focus group discussion (FGD) was employed to collect the data. The participants consisted of 18 students of an English Education Department of a private university in Yogyakarta. The data showed that online discussion had several advantages including interesting learning formats, flexibility, improved ideas and the improvement of writing skills. Of the three stages of the CoI framework including teaching, social and cognitive presence, only one stage had been well articulated, namely cognitive stage.